CORONARY ARTERY CALCIFICATION: PATHOGENESIS AND METHODS OF MYOCARDIAL REVASCULARIZATION - A.S. FYODOROV; A.N. SHISHKEVICH; V.N. KRAVCHUK; SH.M. ASADULAEV; O.YA. POREMBSKAYA; U.M. MURATBEKOVA (Паёми Сино)
The review presents contemporary data on the etiology, pathogenesis, and prevalence of coronary artery calcification (CAC), a significant concern in cardiology. CAC and atherosclerosis of the coronary arteries (CA) are interconnected and may develop concurrently. Various factors contribute to CAC, including genetic predisposition, aging, and comorbidities. Local and systemic factors damage the arterial layers and facilitate the development of atherosclerotic calcium plaques, which are central to the pathogenesis of myocardial vascular calcification. CAC can be categorized into primary and secondary calcification and dystrophic, metastatic, and metabolic types. The extent of calcification is assessed using various methods that help tailor an individual management strategy for patients. Nonetheless, the intravascular diagnosis of calcification and the selection of appropriate techniques for restoring the lumen of affected vessels remain challenging. In mild cases of CAC, the balloon method may be employed, possibly alongside intravascular lithotripsy. Conversely, more severe calcification may require aggressive treatment, including ablative techniques such as rotational and orbital atherectomy. Balloon lithoplasty, due to its ease of use and effectiveness on superficial and deep calcium deposits, is an emerging technology that may take a leading role compared to other treatment methods.